Long non‐coding RNA NR2F1‐AS1 promoted proliferation and migration yet suppressed apoptosis of thyroid cancer cells through regulating miRNA‐338‐3p/CCND1 axis. Issue 9 (14th July 2019) - Guo, Feng; Fu, Qingfeng; Wang, Yang; Sui, Guoqing
Abstract: Thyroid cancer (TC) is a prevalent endocrine malignant cancer whose pathogenic mechanism remains unclear. The aim of the study was to investigate the roles of long non‐coding RNA (lncRNA) NR2F1‐AS1/miRNA‐338‐3P/ CCND1 axis in TC progression. Differentially expressed lncRNAs and mRNAs in TC tissues were screened out and visualized by R program. Relative expression of NR2F1‐AS1, miRNA‐338‐3p and cyclin D1 ( CCND1 ) was determined by quantitative real time polymerase chain reaction. In addition, Western blot analysis was adopted for evaluation of protein expression of CCND1 . Targeted relationships between NR2F1‐AS1 and miRNA‐338‐3p, as well as miRNA‐338‐3p and CCND1 were predicted using bioinformatics analysis and validated by dual‐luciferase reporter gene assay. Besides, tumour xenograft assay was adopted for verification of the role of NR2F1‐AS1 in TC in vivo. NR2F1‐AS1 and CCND1 were overexpressed, whereas miRNA‐338‐3p was down‐regulated in TC tissues and cell lines. Down‐regulation of NR2F1‐AS1 and CCND1 suppressed proliferation and migration of TC cells yet greatly enhanced cell apoptotic rate. Silence of NR2F1‐AS1 significantly suppressed TC tumorigenesis in vivo. NR2F1‐AS1 sponged miRNA‐338‐3p to up‐regulate CCND1 expression to promote TC progression. Our study demonstrated that up‐regulation of NR2F1‐AS1 accelerated TC progression through regulating miRNA‐338‐3P/ CCND1 axis.